Correlation Analysis Between Modic Change of Cervical Vertebrae and Intramedullary High Signal Intensity. Issue 9 (November 2017) - Zhou, Hao; Fan, Jin; Sun, Peng; Zhou, Wei; Li, Qingqing; Yu, Lipeng; Yin, Guoyong
Abstract : Purpose: Clinical studies have shown that endplate Modic change in the cervical spine and intramedullary high signal intensity often occurs simultaneously. We aimed to investigate whether there is a correlation between Modic change and intramedullary high signal intensity, and to explore the possible risk factors. Materials and Methods: In total, 133 patients with cervical spondylotic myelopathy treated at the First Affiliated Hospital of Nanjing Medical University between May 2009 and March 2013 were enrolled in the study. Preoperative cervical magnetic resonance imaging and radiographs in hyperextension and hyperflexion were analyzed. With regard to magnetic resonance imaging, all patients were classified into groups according to Modic change types and intramedullary high signal intensity; the ratio of spinal cord compression reflected the degree of spinal stenosis. For plain radiographs, total range of motion (ROM) and segmental ROM of the cervical vertebrae were measured. Results: Modic change of the cervical vertebral endplate and intramedullary high signal intensity demonstrated a significantly positive correlation. In patients with Modic change and intramedullary high signal intensity, the segmental angle of motion of the cervical vertebrae in hyperextension, cervical segmental ROM, and ratio of spinal cord compression were significantly higher than in patients without Modic change and intramedullary high signal intensity. Conclusions: The occurrence of Modic change and intramedullary high signal intensity are related to cervical instability and spinal canal stenosis. Severe disc protrusion may cause an increase of ROM in cervical hyperextension. Such patients are more prone to Modic change of the cervical vertebral endplate and intramedullary high signal intensity.